Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1182/blood.v84.8.2759.bloodjournal8482759
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphonuclear neutrophils from human immunodeficiency virus- infected patients show enhanced activation, diminished fMLP-induced L- selectin shedding, and an impaired oxidative burst after cytokine priming

Abstract: Impaired polymorphonuclear neutrophil (PMN) function may contribute to the onset of certain life-threatening bacterial and fungal infections in human immunodeficiency virus (HIV)-infected patients. Published data on PMN functional activity in HIV infection are controversial, possibly because most studies have involved PMNs isolated from their blood environment by means of various procedures that may differently affect surface receptor expression and thereby alter cellular responses. We therefore used flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
31
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 1 publication
(1 reference statement)
7
31
0
Order By: Relevance
“…However, platelet activation may also be related to other manifestations of immunological hyperactivity characteristic of HIV-1 infection. Monocytes and neutrophils, which are persistently activated during HIV-1 infection (25,40), and several inflammatory cytokines (e.g., IL-1 and TNF-a) known to be raised during HIV-1 infection (18,25) appear to promote platelet activation (5,41). Indeed, in the present study there was a significant positive correlation between plasma levels of TNF-a and both the expression of P-selectin on the platelet surface and the amount of microvesicles.…”
Section: Discussionsupporting
confidence: 52%
“…However, platelet activation may also be related to other manifestations of immunological hyperactivity characteristic of HIV-1 infection. Monocytes and neutrophils, which are persistently activated during HIV-1 infection (25,40), and several inflammatory cytokines (e.g., IL-1 and TNF-a) known to be raised during HIV-1 infection (18,25) appear to promote platelet activation (5,41). Indeed, in the present study there was a significant positive correlation between plasma levels of TNF-a and both the expression of P-selectin on the platelet surface and the amount of microvesicles.…”
Section: Discussionsupporting
confidence: 52%
“…Previous [29] and present results show that neutrophils from HIV-infected patients have increased baseline levels of superoxide production, particularly before AIDS is established. Additionally, previous reports have also shown that part of the dysfunction observed in neutrophils from HIVinfected patients is secondary to an altered ROS production [35].…”
Section: Discussionsupporting
confidence: 72%
“…As described previously, phagocytes from HIV-infected patients produce altered levels of superoxide, particularly before acquired immunodeficiency syndrome (AIDS) is established [29,30]. We observed that both freshly isolated and 6 h cultured neutrophils from HIV-infected patients produce increased levels of superoxide when compared with control individuals: 7·3 Ϯ 3·9 versus 2·9 Ϯ 0·8 and 10·1 Ϯ 1·6 versus 4·1 Ϯ 1·5, respectively ( Fig.…”
Section: Increased Superoxide Production In Hiv-infected Patientssupporting
confidence: 65%
“…Three previous reports of leucocyte adhesion molecules in HIV-infected individuals have appeared [14][15][16] and only two of these studied neutrophils. In one, of 42 HIV þ subjects, there were no data concerning risk group, prescribed and unprescribed drug (opiate and NSAID) use, disease stage or presence or absence of intercurrent infections [14]. However, their finding of impaired Lselectin shedding concurs with our own.…”
Section: Discussionmentioning
confidence: 99%